A Potential Role of Bone Morphogenetic Protein 7 in Shell Formation and Growth in the Razor Clam Sinonovacula constricta - Zhao, Jiaxi (Front Physiol, 2020)
Bone morphogenetic proteins (BMPs) not only play essential roles in bone development but also are involved in embryonic growth, organogenesis cell proliferation and differentiation. However, the previous studies on the functions of shellfish BMPs genes are still very limited. To better understand its molecular structure and biological function, BMP7 of the razor clam Sinonovacula constricta (Sc-BMP7) was cloned and characterized in this study. The full length of Sc-BMP7 is 2252 bp, including an open reading frame (ORF) of 1257 bp encoding 418 amino acids. The protein sequence included a signal peptide (1–32 aa), a prodomain (38–270 aa) and a TGF-β domain (317–418 aa). The quantitative expression of eleven adult tissues showed that Sc-BMP7 was significantly higher expressed in the gill, foot, and mantle (P < 0.05), but lower in hemocytes and hepatopancreas. In the early development stages, low expression was detected in the stages of unfertilized mature eggs, fertilized eggs, 4-cell embryos, blastula, gastrulae, whereas it increased after the stage of trochophore and demonstrated the highest expression in umbo larvae (P < 0.01). In shell repair experiment, Sc-BMP7 showed increasing expression level after 12 h. The higher expression of Sc-BMP7 was detected while Ca(2+) concentration was reduced in seawater. After inhibiting Sc-BMP7 expression using RNA interference (RNAi) technology, expression of Sc-BMP7 mRNA and protein were significantly down-regulated (P < 0.05) in the central zone of mantle (nacre formation related tissue) and the pallial zone of mantle (prismatic layer formation related tissue). Association analysis identified two shared SNPs in exon of Sc-BMP7 gene from 246 individuals of two groups. These results indicated that BMP7 might be involved in shell formation and growth. These results would contribute to clarify the role of Sc-BMP7 in the regulation of growth and shell formation, and provide growth-related markers for molecular marker assisted breeding of this species.